Efektifitas Penyuluhan Tentang MPASI Terhadap Pengetahuan Ibu Dalam Pemberian MPASI Pada Balita Usia 6-24 Bulan Di Posyandu Wilayah Kerja Desa Jiwo Wetan - Dynamurti Wintoro, Piscolia; Hartati, Lilik; Kusuma Utari, Yantri (Universitas Muhammadiyah Klaten, 2023)
Based on the preliminary study, it was found that 57 mothers with children aged 6-24 months at the Posyandu in the Working Area of ​​Jiwo Wetan Village. The results of the interviews showed that 3 out of 10 mothers gave complementary foods to their children. Increasing mother's knowledge about proper complementary feeding can be done by conducting health education using counseling methods. This study aims to determine the effectiveness of counseling on mothers' knowledge about giving MP-ASI to toddlers aged 6-24 months. This research method is quasi-experimental with a one-group pretest and posttest design. The sample of this study were all mothers who had children aged 6-24 months who attended counseling about complementary foods at the Posyandu in Jiwo Wetan Village, a total of 32 mothers. The sample technique uses accidental sampling. The instrument used is a questionnaire. Data analysis using Wilcoxon. The results showed that the majority of mothers' knowledge about giving MPASI before counseling was in the sufficient category, as many as 21 people (65.5%), while after counseling it increased, namely the majority in the good category, as many as 28 people (87.5%) with the results of bivariate analysis obtained a p value of 0.000 (p < 0.05). The conclusion of this study is that counseling about MPASI is effective in increasing mothers' knowledge about giving MPASI to toddlers aged 6-24 months at the Posyandu in the Jiwo Wetan Village Working Area. Suggestions for mothers are expected to be active in posyandu activities by following every implementation of counseling from cadres or health workers.